Interaction of 2,4-D with Glyphosate or Graminicides on Grass Weed Control in Enlist E3 Soybeans - R. Liu; I. Effertz; T. Lambert; A. Jhala; V. Kumar (Kansas Agricultural Experiment Station Research Reports, 2021)
The introduction of Enlist E3 soybean allows growers to use postemergence (POST) applications of low-volatile formulations of 2,4-D choline (Enlist One) for in-season control of glyphosate-resistant weeds. The POST applications of Enlist One and glyphosate (Roundup PowerMax) mixture can be tank-mixed with clethodim (Select Max) or quizalofop (Assure II) for both grass and broadleaf weed control. However, reduced control of grass weed species has previously been reported when graminicides (Select Max or Assure II) are tank-mixed with auxinic herbicides (2,4-D or dicamba). The main objective of this research was to determine the effectiveness of Enlist One, Roundup PowerMax, Select Max, and/or Assure II alone or in various combinations on grass weed control in Enlist E3 soybean. Field experiments were conducted during the 2020 growing season at the Kansas State University Agricultural Research Center (KSU-ARC) near Hays, KS, and the University of Nebraska near Lincoln, NE (UNL). The dominant grass species at the KSU-ARC site were southwest cupgrass and green foxtail. The predominant grass species at the UNL site were giant foxtail, hairy cupgrass and fall panicum. Herbicide treatments, including Select Max, Assure II, and Roundup PowerMax applied at V3-V4 soybean stage alone or in combination with Enlist One; and sequential treatments of Enlist One followed by (separated by 5 days) Select Max, Assure II and/or Roundup PowerMax, and vice-versa were investigated. Results from the KSU-ARC site indicated that sequential treatment of Enlist One at 5 days prior to the application of Assure II provided the highest control (87% to 90%) of southwest cupgrass and green foxtail at 28 days after treatment (DAT). In contrast, control of both grass species did not exceed 78% with the rest of the treatments. Soybean grain yields ranged from 7 to 16 bu/a for the majority of the treatments. Results from UNL site showed that the addition of Enlist One to Select Max or Assure II or applied in sequential treatments at 5 days after the application of these graminicides reduced control of giant foxtail (69% to 79%), hairy cupgrass (70% to 79%), and fall panicum (69% to 79%) at 28 DAT compared to graminicides alone (93 to 97%). Furthermore, an addition of Roundup PowerMax to tank-mixtures of Enlist One with Select Max or Assure II improved the control of all three weed species. Soybean grain yields ranged from 21 to 55 bu/a for the majority of the treatments. In conclusion, these results support the hypothesis that Enlist One can compromise the efficacy of Select Max or Assure II; however, addition of Roundup PowerMax to these tank-mixtures can help to optimize grass weed control in Enlist E3 soybean.
Keywords: auxinic herbicides; glyphosate; graminicide; herbicide interaction; 2; 4-D; clethodim; Enlist soybean